Neuroprotection for stroke: current status and future perspectives. - Minnerup, J; Sutherland, B; Buchan, A; Kleinschnitz, C (2012)
Neuroprotection aims to prevent salvageable neurons from dying. Despite showing efficacy in experimental stroke studies, the concept of neuroprotection has failed in clinical trials. Reasons for the translational difficulties include a lack of methodological agreement between preclinical and clinical studies and the heterogeneity of stroke in humans compared to homogeneous strokes in animal models. Even when the international recommendations for preclinical stroke research, the Stroke Academic Industry Roundtable (STAIR) criteria, were followed, we have still seen limited success in the clinic, examples being NXY-059 and haematopoietic growth factors which fulfilled nearly all the STAIR criteria. However, there are a number of neuroprotective treatments under investigation in clinical trials such as hypothermia and ebselen. Moreover, promising neuroprotective treatments based on a deeper understanding of the complex pathophysiology of ischemic stroke such as inhibitors of NADPH oxidases and PSD-95 are currently evaluated in preclinical studies. Further concepts to improve translation include the investigation of neuroprotectants in multicenter preclinical Phase III-type studies, improved animal models, and close alignment between clinical trial and preclinical methodologies. Future successful translation will require both new concepts for preclinical testing and innovative approaches based on mechanistic insights into the ischemic cascade.